Design of beam collection system with high transmission efficiency and tunablity. Issue 1 (1st January 2023) - Yan, Y; Yang, T; Li, D Y; Cheng, H; Li, Y Z; Wu, M J; Fang, Y L; Li, F N; Guo, Z; Yuan, Z X; Zhu, K; Lin, C; et al.
Abstract: A beamline is required to focus proton beams produced by laser plasma accelerator to high charge density spots for practical applications. The Compact LAser Plasma Accelerator (CLAPA) coupled with an image-relaying beamline has been built at Peking University. While the collection section of this beamline is an electromagnetic quadrupoles (EMQs) triplet with certain aperture, more than 71 % of the protons are lost in the inlet end face or vacuum tube wall of triplet due to their divergence angles. Here we show the development of a high transmission efficiency and tunable collection system in the beamline by adding two permanent magnet quadrupoles (PMQs) with magnetic field strengths of about 200 and 120 T/m respectively in front of the triplet. As a result, by monitoring the relative position of the PMQs and the currents of the EMQs, the focusing energy is able to be adjusted ranging from 2 to 10 MeV, and the transmission efficiency is 1.4 to 3 times as high as only collected by EMQs triple.